Heart Diseases Associated Genes - Zahedipour, Fatemeh; Chegeni, Rouzbeh; Gheflat, Shivasadat; Bandehpour, Mojgan (Novelty in Biomedicine, 2020)
Background: Heart diseases are complex pathophysiologic conditions involving biomarkers. Understanding the mechanisms by which a gene selectively triggers intracellular molecular responses provide insight into the complex processes implicated in heart diseases. The aim of this study was to predict heart diseases associated genes. Materials and Methods: A number of computational methods have been developed for human gene prioritization. In this study, we used Beegle and KEGG pathway databases and two online services for gene prioritization and analysis of genes related to heart disease. Results: Over 200 genes and 5 key signaling pathways related to human heart diseases were found. The processes in which gene mutations trigger a response in cells leading to cardiac conditions involve multiple pathways. Conclusion: The genes related to heart diseases could be CRP, NPPB, IL-6, ACE2 and GATA4 with high scores and the researchers should find the diagnostic biomarker between them.